PROFESSIONALIZATION OF TEACHING THROUGH FUNCTIONAL TEACHER EDUCATION IN NIGERIA - Musibau Adeoye, Yusuf; Festus Oluwole, Afolabi; Morakinyo Oyewumi, Oyetayo (European Scientific Journal, ESJ, 2014)
This paper specifically focuses on professionalization of teaching profession through functional Teacher Education in Nigeria. The first part of the paper examines the concept of teaching, professionalization and functional Teacher education in Nigeria. The second aspect examines the strategies for professionalization of teaching in Nigeria. The third aspect focuses on the problems of professionalization of teaching in Nigeria. The paper is concluded with the implication of professionalization of teaching through functional teacher education.